The Influence of Computer Literacy and The Use of The Website to Student’s Motivation in The Job Search Among Vocational Education Students - Dyah Anggun; Taufiq Lilo Adi Sucipto; Dwi Maryono (Pendidikan Teknik Informatika dan Komputer, Universitas Sebelas Maret, 2018)
The objective of research were to find out (1) the influence of computer literacy toward student’s interest in looking for jobs; (2) the influence of website usage as media information toward student’s interest in looking for jobs; (3) The influence of computer literacy and intensity of website usage as media information toward student’s interest in looking for jobs of class XII vocational school at wonogiri district in academic year of 2015/2016.The research used quantitative approach with survey methods.The research used cluster random sampling with result 165 students in 3 district as the samples. Data were collected by questionnaire methods and documentation. The data analysis techniques used to test the hypothesis weresimple regression and multiple regression analysis.The result of this research as follow (1) there were positive and significant influence of computer literacy toward student’s interest in looking for jobs, with correlation coefficient (r) to 0,249 and thitung>ttabel (3,289>1,97); (2) there were a positive and significant influence of website usage as media information toward student’s interest in looking for jobs, with correlation coefficient (r) to 0,316 and thitung>ttabel (4,250>1,97); (3) there were positive and significant influence of computer literacy and intensity of website usage as media information toward student’s interest in looking for jobs of class XII vocational school at wonogiri district in academic year of 2015/2016, with correlation coefficient (r) to 0,361 and Fhitung>Ftabel (12,164>3,05). The magnitude of the influence of computer literacy and intensity of website usage as media information toward student’s interest in looking for jobs simultaneously obtained from the calculation of the R-square of 13%.